The animals : a novel - Kiefer, Christian, 1971- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2015)
"Bill Reed manages a wildlife sanctuary in rural Idaho, caring for injured animals--raptors, a wolf, and his beloved bear, Majer, among them--that are unable to survive in the wild. Seemingly rid of his troubled past, Bill hopes to marry the local veterinarian and live a quiet life together, the promise of which is threatened when a childhood friend is released from prison. Suddenly forced to confront the secrets of his criminal youth, Bill battles fiercely to preserve the shelter that protects these wounded animals and to keep hidden his turbulent, even dangerous, history"--Amazon.com.